MiR-335 is involved in major depression disorder and antidepressant treatment through targeting GRM4. (8th October 2015) - Li, Jing; Meng, Huaqing; Cao, Wan; Qiu, Tian
Highlights: MiR-335 was downregulated in the blood samples of MDD patients. miR-335 can directly target GRM4 and suppress its expression. citalopram upregulated miR-335 and downregulated GRM4. GRM4 can regulate the expression of miR-335. miR-335 was upregulated after citalopram treatment in MDD patients. Abstract: Major depressive disorder (MDD) is a prevalent mood disorder. Treatment of MDD includes a variety of biopsychosocial approaches. Glutamate receptor, metabotropic 4 (GRM4) has been implicated in the regulation of MDD and it is seen as an attractive target for drug discovery and development. Here we reported using cellular assays and blood samples from MDD patients and showed that miR-335 was downregulated in individuals with depression compared with healthy controls. Additionally, we confirmed that miR-335 can directly target GRM4, which can further regulated the expression of miR-335. Antidepressant drug treatment with citalopram can upregulate miR-335 expression and downregulate GRM4 expression. These results suggest that miR-335 is associated with the pathophysiology of depression and is a potential target for new antidepressant treatments.